Evaluation of temperature and moisture response surface on the lipase from pumpkin seeds fermentation using Aspergillus niger - doi: 10.4025/actascitechnol.v34i3.12497 - Santos, Rafaela Cristiane Andrade; Araújo, Kyzzes Barreto de; Soares, Cleide Mara Faria; Aquino, Luciana Cristina Lins de (Acta Scientiarum. Technology, 2012)
Agro-industrial waste has shown great potential for use in solid-state fermentation due to its low cost and promoting the growth of microorganisms. This study evaluated the interaction between temperature and moisture response surface on lipase from the fermentation of pumpkin seed flour, using Aspergillus niger. Fermentations were performed in Petri dishes in an experimental design using a 22 matrix with four replications at the center point and four axial points, varying substrate moisture between 30 and 60% and temperature between 30 and 40ºC. The maximum hydrolytic activity (71.88 U g-1 dry weight) was obtained using flour with 30% moisture and 30°C temperature in 120 hours of fermentation. The interaction between fermentation temperature and initial moisture content of the residue was the parameter that most influenced the process at 95% significance level. The response surface analysis showed that the maximum lipase production can be obtained under temperature and moisture conditions of the flour ranging from 28 to 34.5°C and 25 to 32.5%; or between 32 and 40°C and 58 and 65%, respectively. Pumpkin seed flour showed potential for obtaining microbial lipase.